Advances in site investigation practice proceedings of the international conference held in London on 30-31 March 1995. (Thomas Telford, 1996)
These papers focus on the advances in site investigation practice by looking at the planning, control, data management, drilling, boring, sampling and description. Geophysical and laboratory testing is also discussed.